The relationship between internal environment of corporate entrepreneurship and innovation in private colleges in Perak (IR) - Wu, Jing Nan (2018)
The propose of this study were to investigate the relationship between internal corporate entrepreneurial environment (ICEE) indicators i.e. management support, work discretion, time availability and innovation (INV); and the influence of each indicator of ICEE towards INV. Data were collected from 150 middle managers of 19 private colleges in Perak using systematic random sampling. Descriptive and inferential statistics were applied to analyze the data. The result showed that there was a significant relationship between ICEE (management support, r=.554, p<.01, work discretion, r=.496, p<.01, time availability, r=.462, p<.01) and INV the regression analysis showed that management support (β=.590, p<.01) and work discretion (β=.269, p<.01) contributed the highest than time availability (β=.076, p<.01) toward INV. The regression model indicated 58.8% of the variance in INV can be explained by the above three indicators. In conclusion, the middle managers perceived their management support, work discretion, time availability for corporate entrepreneurship to be positively supportive for innovation activities. The implication of the study will help middle managers and policy makers to get a better understanding of the entrepreneurial process of colleges and design their business strategies towards more entrepreneurial and innovative behaviors.